ANALYSIS OF PRESSURE VARIATION OF FLUID IN AN INFINITE ACTING RESERVOIR (Nigerian Journal of Technology, 2016)
In this work, we investigate the well pressure distribution in a boundless reservoir.  This research work seeks to know the pressure variation in a reservoir whose pressure disturbance caused by the withdrawal of fluid from the wellbore, is yet to be felt at the external boundaries of the reservoir. The diffusivity equation was used in the analysis. The work covers the transient state where the reservoir is acting as if it was infinite in size. The finite element technique, using Lagrange quadratic shape elements was employed to carry out the analysis over the cross-section of the reservoir. The analysis was done with the assumption that before the well begins production, there was uniform distribution of pressure all through the reservoir. The accuracy of the result was validated by comparing with the results published by Chatas and Lee. The comparison shows a strong positive correlation between the two methods. Also, the results published by Chatas and Lee stated only the pressure at the wellbore at a particular time but this work predicts the pressure variation in the entire reservoir from the wellbore to the infinite sized external boundary at the same time.  http://dx.doi.org/10.4314/njt.v36i1.11